Infection Control Practices Among Thai Medical Students - Ruj Nana; Sirashat Hanvivattanakul; Porntita Sae-li; Thana Khawcharoenporn (Journal of Health Science and Medical Research, 2026)
Objective: To assess the knowledge, infection control (IC) practices, and antibiotic prescribing practices of Thai medical students in their clinical yearsMaterial and Methods: A cross-sectional anonymous survey was conducted among 4th- to 6th-year medical students at a Thai public university from January 2023 to February 2024. Data were collected on demographics, knowledge about antibiotics and IC, and patient-related IC practices, as well as antibiotic prescribing practices among 6th-year students. Results: Of the 147 students surveyed, 51% were female, with 35%, 29%, and 36% in the 4th, 5th, and 6th years, respectively. The median knowledge score for antibiotics and IC was 14 out of 18, with 6th-year students scoring significantly higher than the 4th- and 5th-year students. However, only 26.5% reported always washing their hands before patient examinations, and 41.5% always washed their hands after touching patient surroundings. A significantly higher proportion of 4th-year students reported wearing unwashed white coats repeatedly (p-value=0.008). Students from outside Bangkok were more likely to wash their hands consistently before examining patients (odds ratio 6.28; p-value=0.02). Among 6th-year students, 30.2% often or always prescribed antibiotics for asymptomatic bacteriuria, 39.6% empirically prescribed quinolones for urinary tract infections, and 22.7% reported antibiotic resistance in treated patients. Conclusion: The study identified gaps in IC practices and the application of knowledge among medical students. Interventions to improve IC practices are needed.